Establishment of a highly efficient conjugation protocol for Streptomyces kanamyceticus ATCC12853. Issue 6 (17th November 2018) - Zhang, Shuman; Chen, Tiansheng; Jia, Jia; Guo, Liwen; Zhang, Huizheng; Li, Chao; Qiao, Renzhong
Abstract: Kanamycin B as the secondary metabolite of wild‐type Streptomyces kanamyceticus ( S. kanamyceticus ) ATCC12853 is often used for the synthesis of dibekacin and arbekacin. To construct the strain has the ability for kanamycin B production; the pSET152 derivatives from Escherichia coli ET12567 were introduced to S. kanamyceticus by intergeneric conjugal transfer. In this study, we established a reliable genetic manipulation system for S. kanamyceticus . The key factors of conjugal transfer were evaluated, including donor‐to‐recipient ratio, heat‐shock, and the overlaying time of antibiotics. When spores were used as recipient, the optimal conjugation frequency was up to 6.7 × 10 −6 . And mycelia were used as an alternative recipient for conjugation instead of spores; the most suitable donor‐to‐recipient ratio is 1:1 (10 7 :10 7 ). After incubated for only 10–12 hr and overlaid with antibiotics subsequently, the conjugation frequency can reach to 6.2 × 10 −5 which is sufficient for gene knockout and other genetic operation. Based on the optimized conjugal transfer condition, kanJ was knocked out successfully. The kanamycin B yield of kanJ ‐disruption strain can reach to 543.18 ± 42 mg/L while the kanamycin B yield of wild‐type strain was only 46.57 ± 12 mg/L. The current work helps improve the content of kanamycin B in the fermentation broth of S. kanamyceticus effectively to ensure the supply for the synthesis of several critical semisynthetic antibiotics. Abstract : In this study, we established a reliable genetic manipulation system for Streptomyces kanamyceticus . The key factors of conjugal transfer were evaluated, including donor‐to‐recipient ratio, heat‐shock, and the overlaying time of antibiotics. And we knocked out kanJ and found that the knockout of kanJ led to the accumulation of KB. The KB yield of the kanJ‐disruption strain was 10.7‐fold higher than that of the original strain.